Subepithelial connective tissue graft: a case report - Saraiva, Juliana Alcaras [UNESP] (2011)
Introduction and objective: Marginal tissue recession represents a common condition in Periodontology. Miller's Classes I and II recessions, in which the etiological factors are well diagnosed and eliminated, show great predictability of total coverage when the technique of subepithelial connective tissue graft is used. This technique success has been mainly attributed to the double blood supply for graft's nutrition, originating from the connective tissue of both the periosteum and flap. Case report and conclusion: The authors reported a clinical case in which a Miller's Class I recession was treated by the surgical technique of subepithelial connective tissue graft, obtaining total coverage, eliminating the aesthetic deficiency and the dentin hypersensitivity complained by patient.